Multidimensional Analysis of Human Deaths in Europe During The COVID-19 Pandemic in Terms of Economic Security - Bartosz KOZICKI; Jarosław ZELKOWSKI; Agnieszka LISOWSKA (Communications of International Proceedings, 2021)
The article presents a multidimensional data analysis on the number of human deaths in 30 analyzed European countries. The analyzed data was grouped. Then, they were compiled in identical periods in dynamic terms. For data analysis, indices such as arithmetic means, medians and standard deviations were used. The study uses categorized box plots thanks to which the similarities and differences in the number of human deaths in 30 analyzed European countries before the pandemic and during the COVID-19 pandemic were observed. During the research, it was observed, inter alia, that in identical time series (from week 1 to week 17), the highest increase in the arithmetic mean of human deaths between 2020-2021 was in Poland and amounted to 3,398 people.
Keywords: Human Deaths; COVID-19; Economic Security; European Union; Multidimensional Data Analysis